Quality, availability and storage conditions of oxytocin and misoprostol in Malawi - Nhomsai Hagen; Felix Khuluza; Lutz Heide (BMC, 2020)
Abstract Background Postpartum haemorrhage (PPH) is the leading cause of maternal mortality in low- and middle-income countries (LMICs). Oxytocin and misoprostol are used for the prevention and treatment of PPH. However, both medicines are chemically unstable and sensitive to environmental conditions. Previous studies reported a high prevalence of substandard oxytocin and misoprostol preparations in LMICs. Methods In randomly selected health facilities of four districts of Malawi, the availability of oxytocin and misoprostol was determined, and the knowledge of health workers on storage requirements and use of oxytocics was assessed. Temperature loggers were used to record the storage temperature of oxytocics. Samples of oxytocin injections and misoprostol tablets were collected from the health facilities and from wholesalers. Oxytocin samples were analysed for identity, assay (= quantity of oxytocin) and for pH value according to United States Pharmacopeia 40. Misoprostol samples were analysed for identity, assay, dissolution and related substances according to the International Pharmacopeia 2017. Results All visited hospitals and health centers had oxytocin available. At non-refrigerated storage sites, the recorded mean kinetic temperature exceeded the oxytocic's storage temperature stated on the labels in 42% of the sites. At refrigerated storage sites, the required temperature of 2-8 °C was exceeded in 33% of the sites. Out of 65 oxytocin samples, 7 (11%) showed moderate deviations from specification, containing 82.2-86.8% of the declared amount of oxytocin. Out of 30 misoprostol samples, 5 (17%) showed extreme deviations, containing only 12.7-30.2% of the declared amount. The extremely substandard misoprostol was reported to the national authorities and to WHO, leading to an immediate recall of the respective brand in Malawi. The UK-based distributor of this brand closed its business shortly thereafter. Conclusion Availability of oxytocin was excellent in Malawi, and its quality was better than reported in previous studies in other LMICs. However, storage conditions at the health facilities often did not meet the requirements. Extremely substandard misoprostol tablets were found, representing a serious risk to maternal health. This shows the need for continued efforts for quality assurance in medicine procurement and registration, as well as for post-marketing surveillance.